Condiciones de trabajo y satisfacción laboral de enfermeras del centro quirúrgico de un hospital de Trujillo - Jaime Rodríguez, Yajaira del Rosario (2023)
The objective of the cross-sectional descriptive research was to establish the influence of working conditions on the job satisfaction of nurses at the Surgical Center, Víctor Lazarte Echegaray de Trujillo Hospital - 2019. The sample consisted of 20 nursing professionals, using the labor conditions and job satisfaction questionnaire as an instrument. It was obtained as conclusions that 40% of nurses indicated that working conditions are “Regular”, 20% indicated that they are “Good” and 20% indicated that they are “Bad”. Regarding the level of job satisfaction, 55% indicated "moderately satisfied" job satisfaction, 40% indicated that they are "satisfied", while 5% are "dissatisfied." There is a positive relationship between working conditions and job satisfaction in Nurses at the Surgical Center of Víctor Lazarte Echegaray Hospital 2019